Common physiotherapy practices in management of patients with hip replacement at Zambian-Italian Orthopedic Hospital and UTH - Kunda, Sophie M. (Lusaka: University of Zambia , School of Medicine, 2014)
A study undertaken at the physiotherapy departments in UTH and Zambia-Italian orthopedic hospital between March and May 2014. the study was based on determining the common physiotherapy practices in management of patients with hip replacement at the above mentioned institutions.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Physiotherapy.
Includes bibliographical references.
Keywords: Arthroplasty; Arthroplasty, Replacement, Hip